2012
DOI: 10.1097/igc.0b013e31826b1110
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Oncogene Mutations Detected in Early-Stage Low-Grade Endometrial Cancers

Abstract: Objective To describe the pattern and frequency of oncogene mutations in white and African American (AA) women with endometrial cancer, and to determine if racial differences in oncogene mutations exist among women with pathologically similar tumors. Methods Endometrial cancer patients from a large, urban hospital were identified through medical records, and representative formalin fixed paraffin embedded tumor blocks were retrieved. The study sample included 150 patients (84 AA) who underwent total abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Microsatellite instability (MSI) is three times more common in the tumors of Caucasians compared to BoAA women [ 9 ]; whereas BoAA women have higher incidence of TP53 mutations [ 10 ], thought to be related to higher incidence of Type 2 tumors in these patients. Racial differences have also been seen with PIK3CA and KRAS mutations being seen more frequently in BoAA women as compared to Caucasian women in low-grade endometrioid EC [ 11 ]. Unlike the breadth of knowledge regarding the comparison between BoAA and Caucasian women, much less is known about other ethnic minority groups, for example, Asian.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite instability (MSI) is three times more common in the tumors of Caucasians compared to BoAA women [ 9 ]; whereas BoAA women have higher incidence of TP53 mutations [ 10 ], thought to be related to higher incidence of Type 2 tumors in these patients. Racial differences have also been seen with PIK3CA and KRAS mutations being seen more frequently in BoAA women as compared to Caucasian women in low-grade endometrioid EC [ 11 ]. Unlike the breadth of knowledge regarding the comparison between BoAA and Caucasian women, much less is known about other ethnic minority groups, for example, Asian.…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing of liver cancer found that AXIN1 was more frequently mutated in patients with HBV infection, while mutations of its downstream gene CTNNB1 majorly occurred in HCV-associated cases [8, 9]. Racial diversity of endometrial cancers [10] and non-small-cell lung cancer [11] were investigated by comparing somatic mutations in common cancer genes. Their results suggested that the mutation frequencies of some genes vary according to race, which could benefit cancer diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However there was a non-significant trend toward a difference in both high grade ( p = 0.07) and high-risk histology ( p = 0.08) when all 3 cohorts were compared, with Lumbees having a frequency of high-risk cancers between that of Whites and Blacks. Prior studies have demonstrated that Blacks have a higher rate of high-risk endometrial cancer subtypes and a poorer prognosis than Whites ( Cote et al, 2012a , Cote et al, 2012b , Sherman and Devesa, 2003 , Maxwell et al, 2006 , Santin et al, 2005a , Santin et al, 2005b , Setiawan et al, 2007 , Ueda et al, 2008 ). While we did not demonstrate poor cancer outcomes in the Lumbee cohort, the small size of our study likely limits our ability to assess this.…”
Section: Discussionmentioning
confidence: 99%